Synthesis, characterization and photocatalysis of doped TiO2 coated onto glass substrates - Avena, Engelbert F.
Advanced oxidation processes (AOPs) have attracted attention from a lot of researchers due to its application in wastewater treatment. One of theses methods uses TiO2 as a photocatalyst to degrade pollutants. It was also found that doping can enhance the photocatalytic activity of TiOx making degradation faster and efficient. This research focused on a route to synthesize tetrabutylammonium chloride-doped (TBAC-doped) TiO2 coated onto glass surface. The doped and undoped TiO2 were characterized using ultraviolet-visible (UV-Vis) spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, elemental analysis (EA), scanning electron microscopy (SEM), and x-ray diffraction (XRD). It was shown that the TiO2 formed from calcination of TiO2 sol coated onto glass substrates has amorphous structure and nanosized. TiO2 was also successfully doped using TBAC. The photoactivity of the doped TiO2 bound to glass surface was evaluated and compared with the undoped TiO2 bound also to glass surface. Photodecomposition of rhodamine B base dye (RhB base) was used as test sample for the photocatalysis under mixed-light lamp and was investigated using UV-vis spectroscopy and Mass Spectroscopy (MS). The degree of photodeethylation of RhB Base was found to be most enhanced by the doped C (using 4.0% TBAC solution) catalyst as compared to doped B (using 1.0%) TBAC and doped A (using 0.5% TBAC) catalysts, and undoped catalyst. It was also observed that the 1.0 mg loading of this doped C catalyst photodeethylated the RhB much greater than the 0.3 mg loading. The photodeethylation was also enhanced using two mixed-light lamps instead of only one. Furthermore, increasing illumination time also made the degree of photodeethylation to increase. Ninety percent of the RhB base was highly deethylated, i.e. almost all ethyl groups were cleaved off, after six hours of illumination time.
Computer print out.
Keywords: Photocatalysis; Sewage disposal plants